Flagellin administration protects gut mucosal tissue from irradiation-induced apoptosis via MKP-7 activity. Issue 5 (3rd January 2011) - Jones, Rheinallt M; Sloane, Valerie M; Wu, Huixia; Luo, Liping; Kumar, Amrita; Kumar, Matam Vijay; Gewirtz, Andrew T; Neish, Andrew S
Abstract : Background and aims: Radiotherapy for neoplastic disease is associated with significant adverse enteric effects associated with excessive cell death. Ionising radiation induces cell death by a mechanism that is dependent on JNK (c-jun N-terminal kinase) pathway signalling. Additionally, it is known that cells exposed to extracellular bacterial products such as flagellin, pleiotropically activate a number of innate immune pathways, including that of JNK. The JNK pathway controls its own activity by inducing the transcription of mitogen-activated protein kinase phosphatase-7 (MKP-7) which directly targets phosphorylated JNK, thus functioning as a negative feedback loop. Previously, it has been shown that flagellin limits ionising radiation-induced mortality in mice, but the cellular mechanism of protection remained unknown. Methods: Wild-type C57BL/6 or tlr5 −/− C57BL/6 were injected with flagellin 2 h before exposure to irradiation, and their intestines were examined for apoptosis. Candidate proteins mediating cytoprotection from irradiation were identified by expression profiling. One of these candidates, MKP-7, was cloned and packaged into adenovirus particles, used to infect cultured cells, and examined for the extent to which its activity reduced cellular apoptosis by flow cytometry or immunoblot analysis. Results: Flagellin pretreatment protected mice from radiation-induced intestinal mucosal injury and apoptosis via a Toll-like receptor 5 (TLR5)-dependent mechanism. Expression profiling of flagellin-treated mice showed upregulation of MKP-7, an inducible repressor of the JNK pathway. MKP-7 expression reached a maximum at 2 h after flagellin treatment, coinciding with suppression of phosphorylated JNK and JNK pathway inhibition. Furthermore, constitutive MKP-7 expression protected cultured cells from radiation-induced apoptosis. Conclusions: Flagellin is a promising adjuvant for suppressing ionising radiation-induced injury. MKP-7 activity exhibits cytoprotective effects, and is thus a candidate cellular molecule for limiting the damaging effect of radiotherapy on the gastreointestinal system.